2021
DOI: 10.3389/fphy.2021.659782
|View full text |Cite|
|
Sign up to set email alerts
|

Photo-Diodes Based on CH3NH3PbCl3 Perovskite Single Crystals by Epitaxial Growth for Ultraviolet Photo-Detection

Abstract: Organic-inorganic hybrid methylammonium lead halide perovskite MAPbX3 (where MA = CH3NH3, and X = Cl, Br, I) single crystals are potential semiconductors for photo-detection due to their excellent optoelectronic performance. In particular, MAPbCl3 single crystal is a wide-band-gap (2.9 eV) semiconductor which is suitable for ultraviolet (UV) detection. In this work, n−-n+ photo-diodes are fabricated through solution-processed epitaxial growth, growing Bi-doped MAPbCl3 epitaxial layer on MAPbCl3 single crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…The active area of the device is around 8 mm 2 , which is one of the largest active area for reported CH 3 NH 3 -PbCl 3 single crystal photodetectors. [8][9][10][11][12][13] The crystal structure of the CH 3 NH 3 PbCl 3 single crystal and its powder was characterized by X-ray diffraction (XRD) (Rigaku-D-Max Ra system, with Cu Ka radiation operated at 12 kW). The surface morphology of the CH 3 NH 3 PbCl 3 single crystal was characterized by SU8220 scanning electron microscope (SEM).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The active area of the device is around 8 mm 2 , which is one of the largest active area for reported CH 3 NH 3 -PbCl 3 single crystal photodetectors. [8][9][10][11][12][13] The crystal structure of the CH 3 NH 3 PbCl 3 single crystal and its powder was characterized by X-ray diffraction (XRD) (Rigaku-D-Max Ra system, with Cu Ka radiation operated at 12 kW). The surface morphology of the CH 3 NH 3 PbCl 3 single crystal was characterized by SU8220 scanning electron microscope (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] At present, some progress has been made in the research of CH 3 NH 3 PbCl 3 single crystal photodetectors. [8][9][10][11][12][13] For example, Hye Ri Jung et al reported that an Ag/TiO 2 /MAPbCl 3 / TiO 2 /Ag structured photodetector presented a responsivity of 0.004 A W À1 and a detectivity of 1.05 Â 10 10 Jones at 430 nm under 2 V bias voltage. 8 Jingda Zhao et al reported that a nÀ-n+ photodiodes based on CH 3 NH 3 PbCl 3 single crystal exhibited a responsivity of 404.7 mA W À1 , and a detectivity of 4.87 Â 10 11 Jones at 20V.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the thickness of the single crystals will limit the carrier extraction and transmission capacity, and the final device performance and responsiveness are poor. At present, a variety of solution methods have been developed to prepare perovskite single−crystal thin films, which mainly consist of an epitaxial growth method and space−confined methods [ 17 , 18 ]. At present, the growth methods of single crystals are mainly used in ITC [ 19 ], the solution temperature lowering method (SLT) [ 20 ], the antisolvent vapor diffusion crystallization method (AVC) [ 21 ], the solution evaporation method (SE) [ 22 ], and so on.…”
Section: Introductionmentioning
confidence: 99%